A Study on Tense Errors in the Compositions of Secondary Students in Brunei - Hazirah Daud (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
This study examines the errors in tenses made by 34 secondary students in Brunei who were asked to write a short story based on a picture composition, with the focus on testing Krashen's Natural Order Hypothesis (NOH) in L2 acquisition. The objective of the study is to test the theory in NOH that irregular past tense is acquired before regular past tense through the analysis of the errors made in the verbs. The collected data were analyzed based on the four steps of error analysis: identification, description, explanation, and evaluation. The findings suggest that irregular past tense for verbs such as